PERANAN VISUALISASI DALAM PEMBELAJARAN GERAK - Sukadiyanto Sukadiyanto (Universitas Negeri Yogyakarta, 2000)
The purpose of this research is to study contribution of visualization in motor learning. The research population is male and female athletes in Yognkarta. The random sampling technique is utilized to select athletes as the sample of this research. This is a survey research and the data was collected by question- noire technique. There are three (visual, auditory, and Hnesthetic) in each questionnoire. The results of this research factors indicated that the contribution of auditory visual factor is 46.91%o, and kinesthetic factor is 0.24o/o, factor is 52.85%o. The Iargest contribution in visualization among those from the Hnesthetic factor. factors The general conclusion is tlwt learning sport activities need all of those factors, but kinesthetic is the most essential one.. The reason is that learning through direct various experiences will be mueh better than through obseryation. In learning sport sHlls, it is necessary to provide feedback and use audio visual media as aids.